Turning Digital Technology into Performance: Transformation Capability and Digital Culture in MSMEs - Dudi Haryadi; Ahmad Johan (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
While prior research often treats technology adoption as sufficient for performance gains, this study argues that digital technology capability alone is insufficient without transformation capability and cultural readiness. This study examines how digital technology capability improves the operational performance of micro, small, and medium-sized enterprises (MSMEs) by investigating the mediating role of digital transformation capability and the moderating role of digital culture. Data were collected from 300 MSMEs across multiple business sectors in West Java and analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that digital technology capability has a significant direct effect on operational performance and an indirect effect through digital transformation capability. In addition, digital culture significantly strengthens the relationship between digital technology capability and both digital transformation capability and operational performance. This study contributes to the digital transformation and MSME literature by clarifying the hierarchical relationship between technological capability and transformation capability and by demonstrating the boundary condition of digital culture. Practically, the findings suggest that MSMEs should complement technology adoption with capability development and cultural readiness, for example, through structured digital training and leadership support for experimentation, to achieve superior operational outcomes.